The Effect of Incentives in Non-Routine Analytical Team Tasks - Florian Englmaier; Stefan Grimm; Dominik Grothe; David Schindler; Simeon Schudy (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Despite the prevalence of non-routine analytical team tasks in modern economies, little is understood regarding how incentives influence performance in these tasks. In a series of field experiments involving more than 5,000 participants, we investigate how incentives alter behavior in teams working on such a task. We document a positive effect of bonus incentives on performance, even among teams with strong intrinsic motivation. Bonuses also transform team organization by enhancing the demand for leadership. Exogenously increasing teams' demand for leadership results in performance improvements comparable to those seen with bonus incentives, rendering it as a likely mediator of incentive effects.
Keywords: C92; C93; J33; D03; M52; 330; team work; bonus; incentives; leadership; non-routine; exploration